Analysis of the socio-economic development of the regions of Kazakhstan - Baikin , А.К. (BUKETOV BUSINESS REVIEW, 2017)
The article deals with the concept of economic potential. Determine the relevance assessment of the economic potential of the region. The variations of the gross regional product per capita GRP structure, dynamics of a living wage and per capita income per month, indicators of living standards and poverty indicators of industrial production in Kostanai region, labor productivity changes in GRP in some regions of Kazakhstan, as the real indicators help to identify such things as, in what areas to develop and on which the investigated region is expedient markets can win a leading position, in which case the work as a partner, and in any case it is not necessary to function on the market. This paper proposes a number of options for the region. To determine the directions and priorities for the development of a region is proposed: first, to evaluate the current economic state of the region, and secondly, to evaluate the prospects of the leading industries in the third, to explore the development direction of the largest economic entities, and fourthly, to estimate the contribution of these subjects in development of the region. In addition to the above, it is necessary to develop criteria for the division of enterprises according to their participation in the regional process of reproduction. At the core of this approach is the principle of balance between consumption now services financed from the budget of the territory, and the extent of its financial investments in the development of the region.